PROTOTYPING TO DESIGN AN ANAGLYPH 3D IMAGE BASED ON WATERFALL MODEL (Journal of the College of Education for Women, 2019)
In this paper, a discussion of the principles of stereoscopy is presented, and the phasesof 3D image production of which is based on the Waterfall model. Also, the results are basedon one of the 3D technology which is Anaglyph and it's known to be of two colors (red andcyan).A 3D anaglyph image and visualization technologies will appear as a threedimensionalby using a classes (red/cyan) as considered part of other technologies used andimplemented for production of 3D videos (movies). And by using model to produce asoftware to process anaglyph video, comes very important; for that, our proposed work isimplemented an anaglyph in Waterfall model to produced a 3D image which extracted from avideo.